Perancangan Interior Pub dan Bar Di Semarang - Angga Wijaya Chandra (Intra, 2015)
Pub & Bar business is a business that sells a comfortable atmosphere for relaxing and socializing Pub & Bar also often used as a place to hang out or socialize and entertain business associates, but pubs and bars in Indonesia can’t be used to accommodate activities to facilitate business activity, with the concept of